Management Information Systems and Sustainable Innovation in the Digital Era - Az Zahra Salsabilah Lubis; Muhammad Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
The rapid advancement of digital technology has reshaped nearly every aspect of human life, particularly in the fields of business, education, and government. Within this transformation, Management Information Systems (MIS) have become an essential component that supports organizations in making decisions more effectively and efficiently. By enabling integrated, accurate, and timely data management, MIS provides a solid foundation for organizations to continue innovating and adapting to the fast paced demands of globalization and digital transformation. This study aims to explore more deeply how MIS contributes to sustaining long term innovation in the digital era. Using a qualitative method, the research relies on an extensive literature review drawn from credible scientific sources, including textbooks as well as national and international journal articles. The analysis shows that MIS significantly enhances organizational competitiveness, streamlines innovation processes, and strengthens strategic decision making through data driven insights. Furthermore, an effective and well implemented MIS allows organizations to anticipate market changes, respond quickly to emerging opportunities, and maintain operational stability. Overall, the findings highlight that integrated MIS adoption is not only a technological necessity but also a strategic pillar for achieving sustainable innovation across various industry sectors.